EFEKTIVITAS INSTALASI PENGOLAHAN AIR LIMBAH (IPAL) DOMESTIK SISTEM ROTATING BIOLOGICAL CONTACTOR (RBC) KELURAHAN SEBENGKOK KOTA TARAKAN - Rizal .; Encik Weliyadi (Jurnal Harpodon Borneo, 2014)
The effectiveness of domestic waste water treatment plant (WWTP) RBC System (Rotating Biological Contactor), inplemented in WWTP at Kelurahan Sebengkok Kota Tarakan. The objective of this study was to determine the process and effectiveness of domestic waste water treatment plant (WWTP) at Kelurahan Sebengkok Kota Tarakan. This research carried out for 4 months from April to July 2014. The result of this research that the domestic waste water treatment plant (WWTP) at Kelurahan Sebengkok Kota Tarakan is using RBC system (Rotating Biological Contactor), a processing system by using a system of micro-organisme to break down organic materials. Analysis of the results showed that, the level of effectiviness of domestic waste Water treatment water plant RBC system at Kelurahan Sebengkok Tarakan is very effective. 2013 the average level of effectiveness by 69,24 % and in 2014 by 62, 34 %, decline in the level of effectiveness from 2013 to 2014. Key words : Effectiveness, Waste Water Treatment Plant and RBC